2018
DOI: 10.1038/s41590-018-0162-7
|View full text |Cite
|
Sign up to set email alerts
|

TCRs are randomly distributed on the plasma membrane of resting antigen-experienced T cells

Abstract: It is the main function of T cells to identify harmful antigens as quickly and precisely as possible. Super-resolution microscopy data has indicated that global clustering of the T cell receptor (TCR) occurs prior to T cell activation. Such pre-activation clustering has been interpreted as representing a potential regulatory mechanism that fine-tunes the T cell response. We found here that apparent TCR nanoclustering could be attributed to overcounting artifacts inherent to single-molecule-localization microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
109
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 54 publications
8
109
1
Order By: Relevance
“…A recent report (73) suggested that observations of TCR clusters on the T-cell membrane (17,18,20,22,23,48) were due to imaging artifacts, and that all TCR machineries are randomly distributed on the surface of T cells. However, in that paper TCR-stimulated T cells were spread on ICAM-1-coated surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report (73) suggested that observations of TCR clusters on the T-cell membrane (17,18,20,22,23,48) were due to imaging artifacts, and that all TCR machineries are randomly distributed on the surface of T cells. However, in that paper TCR-stimulated T cells were spread on ICAM-1-coated surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…S4a). 3 Further, the magnitude of the localization errors hardly affects the obtained results ( Fig. S4b).…”
mentioning
confidence: 84%
“…S1) For the simulations shown in Fig. S3 and Fig S9., we used blinking statistics determined previously 2 (Rossboth et al, 2018). Localization errors were simulated by spreading these detections using a Gaussian 3 profile centered on the molecule position with a width of 30 nm, which corresponds to typical localization 4 errors achieved in SMLM experiments.…”
Section: Simulation Of Areas Of Enrichment or Depletion Of Biomoleculesmentioning
confidence: 99%
See 2 more Smart Citations